Air pollution and lymphocyte phenotype proportions in cord blood - Hertz-Picciotto, Irva; Herr, Caroline E W; Yap, Poh-Sin; Dostál, Miroslav; Shumway, Robert H; Ashwood, Paul; Lipsett, Michael; Joad, Jesse P; Pinkerton, Kent E; Srám, Radim J (Environmental health perspectives, 2005)
Effects of air pollution on morbidity and mortality may be mediated by alterations in immune competence. In this study we examined short-term associations of air pollution exposures with lymphocyte immunophenotypes in cord blood among 1,397 deliveries in two districts of the Czech Republic. We measured fine particulate matter < 2.5 microm in diameter (PM2.5) and 12 polycyclic aromatic hydrocarbons (PAHs) in 24-hr samples collected by versatile air pollution samplers. Cord blood samples were analyzed using a FACSort flow cytometer to determine phenotypes of CD3+ T-lymphocytes and their subsets CD4+ and CD8+, CD19+ B-lymphocytes, and natural killer cells. The mothers were interviewed regarding sociodemographic and lifestyle factors, and medical records were abstracted for obstetric, labor and delivery characteristics. During the period 1994 to 1998, the mean daily ambient concentration of PM2.5 was 24.8 microg/m3 and that of PAHs was 63.5 ng/m3. In multiple linear regression models adjusted for temperature, season, and other covariates, average PAH or PM2.5 levels during the 14 days before birth were associated with decreases in T-lymphocyte phenotype fractions (i.e., CD3+ CD4+, and CD8+), and a clear increase in the B-lymphocyte (CD19+) fraction. For a 100-ng/m3 increase in PAHs, which represented approximately two standard deviations, the percentage decrease was -3.3% [95% confidence interval (CI), -5.6 to -1.0%] for CD3+, -3.1% (95% CI, -4.9 to -1.3%) for CD4+, and -1.0% (95% CI, -1.8 to -0.2%) for CD8+ cells. The corresponding increase in the CD19+ cell proportion was 1.7% (95% CI, 0.4 to 3.0%). Associations were similar but slightly weaker for PM2.5. Ambient air pollution may influence the relative distribution of lymphocyte immunophenotypes of the fetus.
Keywords: polycyklické sloučeniny; kohortové studie; Cohort Studies; Česká republika; Polycyclic Compounds; lymfocyty; Air Pollution; fetální krev; Fetal Blood; Czech Republic; novorozenec; znečištění ovzduší; lidé; ženské pohlaví; Immunophenotyping; Humans; Lymphocytes; Infant, Newborn; Environmental Exposure; vystavení vlivu životního prostředí; Female; imunofenotypizace